THE EFFECT OF BEET AND DATE JUICE ON CHANGES IN HEMOGLOBIN IN PREGNANT WOMEN WITH ANEMIA2025 - Sutrisni Sutrisni; Putri Wahyu Wigati; Galuh Pradian Yanuaringsih; Halimatus Saidah; Dhita Kris Prasetyanti (Nursing Sciences Journal, 2026)
Anemia in pregnant women contributes to an increased risk of pregnancy complications. Beetroot and dates are known to contain iron, folate, vitamin C, and antioxidants that can support hemoglobin formation. Providing a combination of beetroot and date juice can be an alternative non-pharmacological nutritional intervention to increase hemoglobin levels in pregnant women with anemia. The purpose of this study was to determine the effect of beetroot and date juice on changes in hemoglobin levels in pregnant women with anemia. This study used a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of pregnant women with mild to moderate anemia selected using a purposive sampling technique. The intervention consisted of administering 250 ml of beetroot and date juice once daily for 7 days. Hemoglobin levels were measured before and after the intervention using a hematology analyzer. Data analysis used the Wilcoxon Signed Rank Test. There was an increase in hemoglobin levels after administering beetroot and date juice. The average Hb level of pregnant women after consuming the juice was 12.96 with a standard deviation of 0.9. There was an average increase in Hb levels after consuming beetroot and date juice of 1.29 g%. The results of the hypothesis test using a paired sample t-test showed a p-value of 0.000 with a 95% confidence level (α = 0.05). Beetroot and date juice administration is effective in increasing hemoglobin levels in pregnant women with anemia and can therefore be recommended as a complementary therapy for managing anemia during pregnancy.